2009
DOI: 10.1016/j.neurobiolaging.2007.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen effects on cognition and hippocampal transcription in middle-aged mice

Abstract: Young and middle-aged female mice were ovariectomized and given cyclic injections of either estradiol or vehicle treatments. During the fifth week after surgery the Morris water maze was used to assess cognitive function. Age and treatment effects emerged over the course of spatial training such that middle-aged vehicle treated mice exhibited deficits in acquiring a spatial search strategy compared to younger vehicle treated mice and middle-age estradiol treated mice. Following behavioral characterization, mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
99
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 65 publications
6
99
0
Order By: Relevance
“…Visuospatial ability shows a strong association with age, in both humans and in rodent models (Aenlle et al, 2009;Ennaceur et al, 2008;Hoogendam et al, 2014). This study demonstrated an age-related cognitive deficit in visuospatial memory in healthy middle-aged mice.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Visuospatial ability shows a strong association with age, in both humans and in rodent models (Aenlle et al, 2009;Ennaceur et al, 2008;Hoogendam et al, 2014). This study demonstrated an age-related cognitive deficit in visuospatial memory in healthy middle-aged mice.…”
Section: Discussionsupporting
confidence: 52%
“…Although severe cognitive deficits notably occur in dementia and neurodegenerative diseases, mild cognitive deficits are also prevalent in otherwise healthy older subjects in both humans and in rodent models (Aenlle et al, 2009;Dumas et al, 2013;Ennaceur et al, 2008;Gautam et al, 2011;Gunstad et al, 2006;Salthouse, 2010). Thus, in the following we focus on the physiology of age-related cognitive changes in otherwise healthy middle-aged subjects as such studies may elucidate early changes in mechanisms of age-related cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggest that aged mice adapt to elevated H 2 O 2 . Transcription of genes regulating redox homeostasis increases during middle age (2,4,47). Thus, the increase in GPx1 expression in aged SOD1 mice may represent an adaptive response.…”
Section: Adaptation To Altered Redox Statementioning
confidence: 99%
“…To a large extent, research on estrogen loss in women parallels the work that has been done on testosterone in men, establishing connections with APOE, 37 as well as demonstrating effects on hippocampal structure and gene expression. 38,39 In addition to estrogen, women also experience late-life declines in testosterone. 40 The distinct pattern of age-related changes of testosterone and estrogen in men and women may complicate any potential comparison; nevertheless, the possibility of similar interactions in women warrants future investigation.…”
mentioning
confidence: 99%